2019
DOI: 10.1037/str0000099
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analytic evaluation of stress reduction interventions for undergraduate and graduate students.

Abstract: Growing numbers of students in college or graduate school experience high stress, resulting in adverse emotional, academic, and health outcomes. A variety of stress reduction interventions have been used with students, but their effectiveness has not been systematically examined. We used meta-analysis to evaluate the efficacy of stress reduction interventions for undergraduate and graduate students. Studies (k ϭ 43) that used an appropriate control group and assessed distress before and after intervention were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
111
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 98 publications
10
111
0
8
Order By: Relevance
“…These findings may be partly a result of the intercorrelations between these constructs, the difficulty with teasing apart the unique contributions of each, or issues with measuring these phenomena using self‐reports (Davidson & Kaszniak, ). At the same time, there is a growing evidence that suggests that MC skills may positively impact young people's well‐being and health‐related behaviours (Bamber, Kraenzle Schneider, & Schneider, ; Regehr, Glancy, & Pitts, 2013; Shapiro, Brown, & Astin, ; Yusufov, Nicoloro‐SantaBarbara, Grey, Moyer, & Lobel, ) warranting further examination of the potential benefits during the transition to college. Here we conceptualize these collectively as MC skills.…”
Section: Conceptualizing MC Skills As Coping Resourcesmentioning
confidence: 99%
“…These findings may be partly a result of the intercorrelations between these constructs, the difficulty with teasing apart the unique contributions of each, or issues with measuring these phenomena using self‐reports (Davidson & Kaszniak, ). At the same time, there is a growing evidence that suggests that MC skills may positively impact young people's well‐being and health‐related behaviours (Bamber, Kraenzle Schneider, & Schneider, ; Regehr, Glancy, & Pitts, 2013; Shapiro, Brown, & Astin, ; Yusufov, Nicoloro‐SantaBarbara, Grey, Moyer, & Lobel, ) warranting further examination of the potential benefits during the transition to college. Here we conceptualize these collectively as MC skills.…”
Section: Conceptualizing MC Skills As Coping Resourcesmentioning
confidence: 99%
“…A growing number of higher education students are reported to experience increasingly high levels of distress worldwide (Sharp & Theiler, 2018;Yusufov, Nicoloro-SantaBarbara, Grey, Moyer, & Lobel, 2019), including postsecondary students in the United Kingdom and the United States (American College Health Association, 2014; Royal College of Psychiatrists, 2003;Scanlon, Rowling, & Weber, 2007;Singleton, Bumpstead, O-Brien, Lee, & Meltzer, 2001;University of Leicester, 2002). Test anxiety, anxiety experienced in testing situations, has been identified as one of those areas of major distress for higher education students (Furr, Westegeld, McConnell, & Jenkins, 2001;Szafranski, Barrera, & Norton, 2012) and it is a concern, as it is reported to be related to poorer classroom test performance, lower grades, lower self-esteem, higher levels of neuroticism (von der Embse, Jester, Roy, & Post, 2018), and school dropout (Gerwing, Rash, Gerwing, Bramble, & Landine, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ratanasiripong et al's (2015) study of 60 graduate students proved that biofeedback intervention was a cost-effective tool to help graduate students manage their anxiety and stress. This finding was further supported by a subsequent similar study (Yusufov et al, 2019) which examined the effectiveness of stress reduction interventions for undergraduate and graduate students. The study showed that interventions, like relaxation training, mindfulness-based stress reduction, and psychoeducation were (more) effective in reducing students' anxiety.…”
Section: Sources Of Student Anxietymentioning
confidence: 56%
“…In addition, studies have shown that anxiety can be reduced by training or methods like humor and other interventions (Berk, 2000;Pan & Tang, 2004;Pelton, 2014;Ratanasiripong, Kaewboonchoo, Ratanasiripong, Hanklang, & Chumchai, 2015;Yusufov et al, 2019). For example, Berk's (2000) 6-year long study showed that humor reduced anxiety in both undergraduate and graduate students and improved their performance.…”
Section: Sources Of Student Anxietymentioning
confidence: 99%